Original paperComparison of inflammatory markers in non-dipper hypertension vs. dipper hypertension and in normotensive individuals: uric acid, C-reactive protein and red blood cell distribution width readings - Tosu, Aydın Rodi; Demir, Serafettin; Selcuk, Murat; Kaya, Yuksel; Akyol, Aytac; Ozdemir, Mahmut; Tenekecioglu, Erhan (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Aim : In this study, we investigated the relationship of increased inflammatory parameters (C-reactive protein – CRP), oxidative stress markers (serum uric acid – SUA) and red blood cell distribution width (RDW) with non-dipper hypertension (NDHT). Material and methods: Among the individuals who presented to the cardiology clinic, 40 patients (32.5% male, 67.5% female; mean age: 54.4 ±7.1) who had hypertension and were diagnosed with NDHT through ambulatory blood pressure monitoring, 40 age- and sex-matched dipper hypertension (DHT) patients (25% male, 75% female, mean age: 54.2 ±7.0), and 40 normotensive individuals (42.5% male, 57.5% female, mean age: 51.9 ±9.0) were enrolled in the study. Peripheral venous blood samples were collected from all the patients in order to evaluate the hematological and biochemical parameters. All the assessed parameters were compared among the groups. Results : The CRP, RDW and uric acid levels were observed to be significantly higher in the non-dipper hypertension group in comparison to the dipper hypertension patients and the normotensive population (p < 0.05). These parameters were also significantly higher in the dipper HT group compared to the normotensive population (p < 0.05). Conclusions : We found in our study that increased CRP, uric acid and RDW levels, which are indicators of increased inflammation and oxidative stress, are significantly higher in the non-dipper HT patients in comparison to the dipper HT patients and control group.